2013
DOI: 10.1073/pnas.1312235110
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus tegument protein pp150 acts as a cyclin A2–CDK-dependent sensor of the host cell cycle and differentiation state

Abstract: Upon cell entry, herpesviruses deliver a multitude of premade virion proteins to their hosts. The interplay between these incoming proteins and cell-specific regulatory factors dictates the outcome of infections at the cellular level. Here, we report a unique type of virion-host cell interaction that is essential for the cell cycle and differentiation state-dependent onset of human cytomegalovirus (HCMV) lytic gene expression. The major tegument 150-kDa phosphoprotein (pp150) of HCMV binds to cyclin A2 via a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 40 publications
3
41
0
Order By: Relevance
“…It is only when cells are infected in S phase, where there are already high levels of cyclin A2, that it might be necessary for UL21a to degrade the cyclin A2 in order for the infection to initiate. The situation is likely more complicated, as it has been reported that the HCMV tegument protein pp150 also binds to cyclin A2, and this binding between pp150 on the incoming particle and cyclin A2 is responsible for the block in initiation of HCMV IE gene expression when cells are infected in S phase (50,51). We cannot exclude that increases in cyclin A2 contribute to the growth deficiency of our double mutant.…”
Section: Discussionmentioning
confidence: 89%
“…It is only when cells are infected in S phase, where there are already high levels of cyclin A2, that it might be necessary for UL21a to degrade the cyclin A2 in order for the infection to initiate. The situation is likely more complicated, as it has been reported that the HCMV tegument protein pp150 also binds to cyclin A2, and this binding between pp150 on the incoming particle and cyclin A2 is responsible for the block in initiation of HCMV IE gene expression when cells are infected in S phase (50,51). We cannot exclude that increases in cyclin A2 contribute to the growth deficiency of our double mutant.…”
Section: Discussionmentioning
confidence: 89%
“…Infection also alters expression of cellular gene products involved in cell cycle regulation, DNA damage-repair, and intrinsic defense mechanisms (25)(26)(27)(28)(29)(30). For example, cellular cyclin A2-CDK inhibits HCMV IE gene expression (31,32) and promotes quiescent infection (33), while p53, a cell cycle regulator, is required for efficient HCMV replication (28,34).…”
mentioning
confidence: 99%
“…Cells in G 0 or G 1 are permissive to initiation of viral immediate early gene expression during lytic infection. In contrast, expression is inhibited during S, G 2 , and M and involves an interaction between cyclin A and the viral protein pp150 (33,34). Lytic infection with HCMV results in a pseudocell cycle phase characterized by inhibition of cellular DNA synthesis along with processes that normally occur during the G 1 /S transition or mitosis (35)(36)(37)(38)(39)(40)(41)(42).…”
mentioning
confidence: 99%